The interpretation of the green economy concept within two major banks in South Africa - Naude, Ruan (My University, 2020)
Globally an unprecedented challenge, in terms of complexity and extent, is facing us all — irrespective of whether some continue to deny its very existence (McCright & Dunlap, 2011). This challenge is the ever-increasing levels of unsustainable resource use leading to ecological degradation and destruction, biodiversity loss and climate change (Hamilton et al., 2015). A concept that has been used to describe the epoch (not the era) in which we find ourselves is that of the Anthropocene (Crutzen, 2006). It has been argued that this epochal moment requires a systemic response in terms of our thinking and practice in all domains of human activity and interaction (Berkhout, 2014) — including but not limited to those of education, work and the interaction between the two. This study, which utilised a case study approach, examined how two major banks in South Africa were interpreting the green economy. In order to analyse the interpretation of the green economy within the two banks, a typology developed by Peter Ferguson which classifies green economy discourses on a continuum from weak green economy discourses to strong green economy discourses, was utilised (2015). The study also examined the interplay between higher education, and specifically the discipline of banking and economics, as banking still employs large numbers of commerce graduates. It illustrated that there were dynamics operational in both domains, banking and economics, that were potentially inhibiting a substantive socio-environmental economic transformation. Furthermore, it showed that the interaction between the two domains is complex; it is problematic to assume a clear and simple link can be established between the two.
A dissertation submitted in fulfilment of the requirements of the degree of Master of Education by Coursework and Research Report to the School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020
Keywords: Sustainable development; Economic development